2011
DOI: 10.1371/journal.pone.0027432
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Responses to Stress after Stress Management Training in Patients with Rheumatoid Arthritis

Abstract: BackgroundStress management interventions may prove useful in preventing the detrimental effects of stress on health. This study assessed the effects of a stress management intervention on the psychophysiological response to stress in patients with rheumatoid arthritis (RA).MethodsSeventy-four patients with RA, who were randomly assigned to either a control group or a group that received short-term stress management training, performed a standardized psychosocial stress task (Trier Social Stress Test; TSST) 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 76 publications
3
43
0
Order By: Relevance
“…Similar to the results of other studies (25,26,29), our CBS also led to lower cortisol secretion under acute stress. However, we did not find a corresponding benefit for clinical data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the results of other studies (25,26,29), our CBS also led to lower cortisol secretion under acute stress. However, we did not find a corresponding benefit for clinical data.…”
Section: Discussionsupporting
confidence: 91%
“…Cognitive behavioural stress management programmes (CBS) have been shown to reduce cortisol responses to laboratory stress in healthy participants and patients with rheumatoid arthritis and to improve psychological and immunological functions in patients with HIV (25)(26)(27)(28)(29). The few studies evaluating psychological interventions (some of which also include stress management) in patients with AD found positive effects on skin status as well as on itch and scratching behaviour (30)(31)(32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%
“…Individual counselling by OTs and PTs led to increased use of self-management strategies, such as hand exercises, joint protection and activity regulation 26 71 72. Individual counselling by psychologists reduced depression, anxiety and total use of healthcare 37 42 69. Individual counselling supplementary to physical exercise improved health status, adherence with exercise programmes and physical activity recommendations 29 50 51 80 84.…”
Section: Resultsmentioning
confidence: 99%
“…Improvements have been found in several aspects of patient functioning, including depression and anxiety, pain and fatigue, medication adherence, and disability, although the evidence for long-term effectiveness has not consistently been studied [3,8,65e70]. Cognitive-behavioral interventions that have shown consistent small to moderate effects in patients with inflammatory rheumatic diseases include coping skills training, stress management training, motivational exercise interventions, and emotional disclosure or therapeutic writing interventions [50,71e75] in some studies, these interventions have shown to affect psychophysiological response systems and diseaserelevant immune parameters such as proinflammatory cytokines [72,76,77].…”
Section: Psychological Interventions In Inflammatory Rheumatic Diseasesmentioning
confidence: 99%